El cuerpo como distopía: un análisis poshumano de la obra de Nee Barros - Alonso Alonso, Maria (Moderna Språk, 2024)
Posthumanism is a barely explored avenue of research in Galician Studies, despite the growing number of literary works published in recent years that illustrate the increasing social debates that have flourished in the last few decades and which are directly connected to this line of thought. Issues related to abject citizenship, figures of exclusion, disposable subjects, among others, appear in works by contemporary authors in the Galician language such as Nee Barros, a transversal and multidisciplinary author who, in recent years, has published an interesting corpus of analysis. This article aims to focus on three of their first works, 19 poemas para um VÍRUS-19 (2020), Identidade (2021) and Nom estamos quebrades (2023). The subjectivity of the human body is the central theme that unites this collection of poems, a play and a novel, respectively; texts that illustrate Barros’s particular sense of transgender lyricism, which questions gender performance as ‘normative’. Posthuman theory will serve in this particular case to explore the way in which Barros interrogates human corporality and the constant scrutiny of non-binary bodies and/or sexualities in the, sometimes, dystopian reality inhabited by subjects who go beyond the limitation imposed by the humanistic male/female gender dichotomy.